Tuberculose: prova intradérmica dupla. Seu uso em saúde pública e em elucidação de diagnóstico - Correa, W. M. (1980)
The Mantoux test and a double intradermal tuberculin test (PID), were carried out on 131 patients hospitalized for diagnostic elucidation. Comparison was made between the results of the two intradermal tests and the final diagnosis, obtained by clinical, surgical and laboratory methods, and the data were submitted to statistical analysis. Measuring Mantoux reaction after 72 h, and injecting a new intradermal dose of PPD at exactly the same point and repeating the reading after another 24 h, the difference in size (mm) between the first and second readings may be interpreted in three different ways: 1) A difference of less than 3 mm between the two readings: nill statistical probability of patient with tuberculosis. 2) A difference of 3 mm or more, with maximal reaction diameter of 9 mm: indecisive result; patient probably without tuberculosis, however it is suggested that a new PID should be carried out after another 90 days. 3) A difference of 3 mm or more, with maximal reaction of 10 mm or more: patient probably has tuberculosis. The statistical analysis showed that the PID test is better than the Mantoux test, presenting fewer errors, less false-positive results, nill probability of false-negative results, better sensibility and specificity. The conclusion was drawn that the PID is a test that can be used in diagnostic elucidation and publici health surveys on the incidence of tuberculosis.